Right to the City? An Analysis of the criminalisation of the informal sector in Harare, Zimbabwe - Elmond Bandauko; Gladys Mandisvika (Centre for Behaviour and Wellness Advocacy, 2015)
This paper seeks to examine the criminalisation of informal sector operations in Harare. The responsible authorities have often viewed the informal sector as being atomistic to the formal economy, a development which has led to the harassment, arrests of informal sector operators in Harare. This phenomenon raises many questions which include, whose city is it anyway? Do informal sector workers have the right to the city? To answer some of these questions, the paper makes use of secondary sources of data such as newspapers, journal articles, magazines, research reports among others. The Government and local authorities should view the informal sector as an integral part of the urban economic system and should thus accommodate it for socially just cities to be created.